2021
DOI: 10.30699/ajnmc.29.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Misoprostol and Evening Primrose oil Capsules with Misoprostol on Delivery Method in Post-Term Pregnancy: Clinical Trial

Abstract: Introduction: Post-term pregnancies are pregnancies that last more than 42 full weeks (294 days) from the first day of the last menstrual period. With increasing gestational age, the rate of maternal and fetal morbidity and mortality significantly increases. Among medical methods, misoprostol is widely used to prepare the cervix in post-term pregnancies. But today, due to the high side effects of misoprostol, especially the increasing need for cesarean section, some complementary medicine methods are used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The findings of the present study on the better efficacy of EPO compared to misoprostol are important because misoprostol is currently widely used for cervical dilation in gynecological procedures. However, as mentioned earlier, misoprostol has unpleasant adverse effects 2,9,20–22 . Consequently, EPO, which is a vegetable oil, has fewer side effects, lower price, and easier availability 11,15–18,23,24 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings of the present study on the better efficacy of EPO compared to misoprostol are important because misoprostol is currently widely used for cervical dilation in gynecological procedures. However, as mentioned earlier, misoprostol has unpleasant adverse effects 2,9,20–22 . Consequently, EPO, which is a vegetable oil, has fewer side effects, lower price, and easier availability 11,15–18,23,24 …”
Section: Discussionmentioning
confidence: 96%
“…However, as mentioned earlier, misoprostol has unpleasant adverse effects. 2,9,[20][21][22] Consequently, EPO, which is a vegetable oil, has fewer side effects, lower price, and easier availability. 11,[15][16][17][18]23,24 Carreon and Gladys 24 compared the effect of oral EPO with vaginal dinoprostone in cervical preparation in hysteroscopic candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of the latent phase in the intervention group decreased, and the Bishop score increased [ 12 ]. In this regard, Bahmani et al’s study also showed that vaginal EPO capsule plus misoprostol is more effective than sublingual misoprostol in cervical preparation [ 18 ]. Another study compared the vaginal administration of EPO capsules with misoprostol to dilate the cervix before gynecological procedures; it reported that cervical dilatation in the EPO group reached an appropriate level in a shorter time than in the misoprostol group [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Najafi et al showed that vaginal administration of EPO capsules reduced the need for labor induction in the intervention group compared to the control group [ 30 ]. Also, the findings of another study showed that the use of vaginal EPO capsules plus misoprostol for cervical ripening in women with prolonged pregnancies is much more effective than misoprostol alone [ 18 ]. Nouri et al reported that EPO capsules were superior to misoprostol for cervical preparation before gynecological procedures [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation